Fertilizer 15N balance in a soybean–maize–maize rotation system based on a 41-year long-term experiment in Northeast China - Dai, Jian; Gui, Hailong; Shen, Feng; Liu, Yuying; Bai, Minsong; Yang, Jinfeng; Liu, Houjun; Luo, Peiyu; Han, Xiaori; Siddique, Kadambot H. M. (Frontiers in Plant Science, 2023)
Global awareness of the need to enhance crop production and reduce environmental issues associated with nitrogen (N) fertilizer has increased. However, studies on how the N fate changed with manure addition are still limited. We undertook a field 15N micro-plot trial in a soybean–maize–maize rotation during 2017–2019 within a 41-year experiment in Northeast China to evaluate the effect of fertilization regimes on soybean and maize yields and the fertilizer N fate in the plant–soil system. Treatments included chemical N alone (N), N and phosphorus (NP), N, P, and potassium (NPK), and those combined with manure (MN, MNP, and MNPK). Application of manure increased grain yield, on average, by 153% for soybean (2017) and 105% and 222% for maize (2018 and 2019) compared to no manure, with the highest at MNPK. Crop N uptake and that from labeled 15N-urea also benefited from manure addition, mainly partitioned to grain, and the average 15N-urea recovery was 28.8% (soybean) and 12.6%, and 4.1% (maize). Across the three years, the fertilizer 15N recovery ranged from 31.2–63.1% (crop) and 21.9–40.5% (0–40 cm soil), with 14.6–29.9% unaccounted for, including N losses. In the two maize seasons, manure addition significantly increased the residual 15N recovery in crop and reduced that in soil and unaccounted for compared to single chemical fertilizer, with MNPK performing the best. Therefore, applying N, P, and K fertilizers in the soybean season and NPK combined with manure (13.5 t ha–1) in the maize seasons is a promising fertilization management strategy in Northeast China and similar regions.